Plan de marketing para el comercial Le Gino ubicado en Chone - Espinoza Basurto, Kenya Jasmín (2023)
The objective of this investigation is to design a marketing plan to strengthen the positioning in the market of the commercial Le Gino in the city of Chone, taking into account the specific objectives, a situational diagnosis of the current state of the commercial in which it was executed was carried out. the interview with the person in charge of the commercial, learning more about the business situation, which allowed the realization of the SWOT matrix of the commercial; internal and external analysis; the analysis of the external factors evaluation matrix and the internal factors matrix, in which it was considered that the business is above average, this because it takes advantage of opportunities in 1.67 surpassing threats of 0.91 and strengths have a value of 2.35, minimizing weaknesses with 0.44, respectively in both matrices and the analysis of Porter's 5 forces. In the same way, a market study was carried out in which the sample size of the population was determined for the application of the survey to a total of 278 people, in addition, the data obtained from said survey were tabulated and graphically represented with its respective analysis for a better understanding, knowing that 90.90% of the population has consumed commercial products. And finally, the action plan was proposed, detailing the strategic objectives and strategies based on the marketing-mix with its activities so that the proposed objectives are met.